2012
DOI: 10.1002/sca.21061
|View full text |Cite
|
Sign up to set email alerts
|

Roughness statistical influence on cell adhesion using profilometry and multiscale analysis

Abstract: In this study, two series of 11 samples of TiAl6V4 titanium alloy and 316L stainless steel have been polished in an isotropic manner at different levels in order to quantify the influence of biomaterial roughness on cell behavior. Topography was measured by a tactile profilometer and a multiscale analysis has been carried out. Human osteoblasts have been cultured on those samples. It appears that roughness has no reproducible effect on the cell behavior except an influence on cell orientation on the wider groo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Therefore, similar effects of the nanoscale EP and the roughness of the CP coatings on SCs were studied using HLPSCs. As discussed in previous studies [ 22 , 23 , 24 ], an original statistical approach was developed for characterizing the relationship between surface roughness and cell adhesion. For two materials, 316L stainless steel and TiAl6V4 titanium alloy, a relationship between R a and cell adhesion has not been found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, similar effects of the nanoscale EP and the roughness of the CP coatings on SCs were studied using HLPSCs. As discussed in previous studies [ 22 , 23 , 24 ], an original statistical approach was developed for characterizing the relationship between surface roughness and cell adhesion. For two materials, 316L stainless steel and TiAl6V4 titanium alloy, a relationship between R a and cell adhesion has not been found.…”
Section: Discussionmentioning
confidence: 99%
“…No relation was found between the roughness amplitude, R a , and cell adhesion. The parameter that better discriminates adhesion is the mean distance between asperities ( S m ); however, this correlation is insufficiently strict, and several authors [ 22 , 23 , 24 ] have developed a new parameter called “adhesion power”.…”
Section: Introductionmentioning
confidence: 99%
“…Grinding processes differ from 1000 to 4000 mesh papers and are only seldom followed by diamond paste polishing. Surface treatments such as mechanical polishing or electrolytic polishing enhance the corrosion resistance, while an increased surface roughness amplitude with a low surface organization increases the corrosion rate [38]. It has been previously demonstrated that surface roughness amplitude has an influence on the corrosion rate of biodegradable materials and consequently the concentration of released species [39,40].…”
Section: Amentioning
confidence: 99%
“…Several techniques involving etching and particle impact can be used to change topography and wettability [5]. A recent study involving isotropic abrasion of both 316L stainless steel and TiAl6V4 and introduction of human mesenchymal stem cells found no statistical effect of roughness on cell number or coverage at 48 h [6]. The main applications as a biomaterial are for femoral heads for total hip replacement where it has been used for more than a decade [7] and dental implants.…”
Section: Introductionmentioning
confidence: 98%